Innovative linguistics in the master's degree: the author's view Floriy Batsevich (article-review of the publication: Fundamentals of linguistic narratology: textbook / Floriy Batsevich. Lviv: Ivan Franko National University of Lviv, 2025. 292 p.) - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2025)
Innovative linguistics in the master's degree: the author's view Floriy Batsevich (article-review of the publication: Fundamentals of linguistic narratology: textbook / Floriy Batsevich. Lviv: Ivan Franko National University of Lviv, 2025. 292 p.)
Keywords: innovative linguistics; Floriy Batsevych; linguo-narratology; author's point of view